Niclosamide inhibits epithelial-mesenchymal transition and tumor growth in lapatinib-resistant human epidermal growth factor receptor 2-positive breast cancer. (February 2016) - Liu, Junjun; Chen, Xiaosong; Ward, Toby; Mao, Yan; Bockhorn, Jessica; Liu, Xiaofei; Wang, Gen; Pegram, Mark; Shen, Kunwei
Highlights: EMT is associated with lapatinib resistance in HER2 positive breast cancer. Lapatinib resistance exhibits a stem-like phenotype and pathways activation. Niclosamide inhibits lapatinib-resistant cell proliferation and stem-like phenotype. Niclosamide ameliorates the EMT phenotype by inhibiting NF-k B and Src pathways. Abstract: Acquired resistance to lapatinib, a human epidermal growth factor receptor 2 kinase inhibitor, remains a clinical problem for women with human epidermal growth factor receptor 2-positive advanced breast cancer, as metastasis is commonly observed in these patients. Niclosamide, an anti-helminthic agent, has recently been shown to exhibit cytotoxicity to tumor cells with stem-like characteristics. This study was designed to identify the mechanisms underlying lapatinib resistance and to determine whether niclosamide inhibits lapatinib resistance by reversing epithelial-mesenchymal transition. Here, two human epidermal growth factor receptor 2-positive breast cancer cell lines, SKBR3 and BT474, were exposed to increasing concentrations of lapatinib to establish lapatinib-resistant cultures. Lapatinib-resistant SKBR3 and BT474 cells exhibited up-regulation of the phenotypic epithelial-mesenchymal transition markers Snail, vimentin and α-smooth muscle actin, accompanied by activation of nuclear factor-кB and Src and a concomitant increase in stem cell marker expression (CD44 high /CD24 low ), compared to naive lapatinib-sensitive SKBR3 and BT474 cells, respectively. Interestingly, niclosamide reversed epithelial-mesenchymal transition, induced apoptosis and inhibited cell growth by perturbing aberrant signaling pathway activation in lapatinib-resistant human epidermal growth factor receptor 2-positive cells. The ability of niclosamide to alleviate stem-like phenotype development and invasion was confirmed. Collectively, our results demonstrate that lapatinib resistance correlates with epithelial-mesenchymal transition and that niclosamide inhibits lapatinib-resistant cell viability and epithelial-mesenchymal transition. These findings suggest a role of niclosamide or derivatives optimized for more favorable bioavailability not only in reversing lapatinib resistance but also in reducing metastatic potential during the treatment of human epidermal growth factor receptor 2-positive breast cancer.